Effect of Trace Rare Earth Elements (Ce) on the Corrosion Resistance of High-Strength Weathering Bridge Steels - Jiquan Chen; Ruifeng Dong; Yuansu Lei; Peiying Zhou; Xiong Yang; Lifeng Fan (Metals, 2025)
In this study, Q370qENH high-strength weathering bridge steel was used as the base material. The corrosion experiment in a marine atmosphere was simulated by the salt spray test, and the outdoor atmospheric exposure corrosion experiment and electrochemical method test were carried out. The corrosion behavior of Q370qENH high-strength weathering bridge steel in a marine atmosphere was studied using electron probe microanalysis (EPMA), field emission scanning electron microscopy (FE-SEM), X-ray diffraction (XRD), and other surface testing techniques. The results show that the corrosion rate of the steel gradually decreases with the increase in the content of trace rare earth elements. Ce played a role in the modification of inclusions so that MnS was modified into rare earth composite inclusions, which slowed down the occurrence of corrosion. The enrichment of Cu alloy elements in the inner rust layer of the rare earth experimental steel improves the compactness of the rust layer, and the thickness of the inner rust layer is increased by 42%, which enhances the stability of the rust layer. With the increase in cerium, the protection coefficient α/γ* of the rust layer of experimental steel increases, indicating that the corrosion resistance of the material is improved. In addition, the electrochemical results show that the addition of rare earth elements in Q370qENH steel will lead to a positive shift in the electrochemical self-corrosion potential, a larger impedance radius of the steel rust layer, and a stronger protective effect. Due to the addition of trace cerium, the seawater corrosion resistance of the test steel is improved.